ASIA SPINE: The Past, Present, and Future - Dong Ah Shin; Young Soo Kim; Hiroshi Nakagawa; Jung Keun Suh; Se-Hoon Kim (Neurospine, 2018)
The sharing of international academic accomplishment and friendship is important; furthermore, to better understand and anticipate the future, we should look back and remember where we started. Regarding ASIA SPINE, the authors aimed to record how the pioneers of Asian spinal surgery started this spine meeting series more than 20 years ago and that later developed into the present state of the conference. The authors will also explore the possible future of this conference. In June 1996, when Professor Hiroshi Nakagawa organized the 11th Annual Meeting of the Japanese Society of Spinal Surgery, spinal neurosurgeons from Korea and Japan including Professor Young Soo Kim, Professor Jung Keun Suh, and Professor Nakagawa discussed the establishment of a multinational conference on spinal surgery via a partnership between the 2 countries. Finally, from September 18 to 20, 1997, the First Biennial Meeting of the Japan-Korea Conference on Spinal Surgery was held in Nagoya, Japan, with Professor Hiroshi Nakagawa as the first organizing President. From then, a biennial meeting was held every other year in Korea or Japan until 2009. In September 2010, the next generation of spinal neurosurgeons decided to organize the first meeting of ASIA SPINE in Incheon, Korea, in order to represent all Asian spine specialists. This meeting has been since held annually around the region including in Taiwan. Remembering the pioneers in the field of spinal surgery is invaluable and extremely important. The authors hope that interest in ASIA SPINE will further expand to other nations in Asia who have advanced philosophies and refined technologies. We wish ASIA SPINE continued success and the ability to promote prolonged international friendship among the Asian countries.